The Relative Contribution of Plasma Homocysteine Levels vs. Traditional Risk Factors to the First Stroke: A Nested Case-Control Study in Rural China - Zhou, Feng; Liu, Chengzhang; Ye, Lijing; Wang, Yukai; Shao, Yan; Zhang, Guohua; Duan, Zhenpeng; Chen, Jingjuan; Kuang, Jingyun; Li, Jingyi; Song, Yun; Liu, Lishun; et al. (Frontiers in Medicine, 2022)
Background: Approximately 75% of Chinese hypertensive patients have elevated homocysteine (Hcy). Its implication in risk assessment and prevention of first stroke remains an important clinical and public health question. Methods: This study was based on a community cohort recruited from 2016 to 2018 in rural China. To maximize cost efficiency, we used a nested case-control design, including 3533 first stroke cases and 3533 controls matched for age ±1 years, sex, and village. Individual associations of tHcy and traditional risk factors with first stroke were examined, and their population-attributable risks (PARs) were estimated. Results: There was a significant dose-response association between first stroke and total Hcy (tHcy) levels, with adjusted odds ratios of 1.11 (95% confidence interval: 0.97, 1.26) for tHcy 10-15 μmol/L and 1.44 (1.22, 1.69) for tHcy ≥15 μmol/L, all compared to tHcy <10 μmol/L. A similar trend was found for ischemic and hemorrhagic stroke. tHcy and systolic blood pressure (SBP) were independently and additively associated with the risk of first stroke [tHcy: 1.06 (1.02, 1.1); SBP: 1.13 (1.1, 1.16); P-interaction, 0.889]. Among the ten main risk factors examined, the top two contributors to first stroke were SBP and tHcy, with PARs of 25.73% and 11.24%, respectively. Conclusions: Elevated tHcy is the second most important contributor and act additively with SBP to increase the risk of first stroke. This finding underscores the importance of screening and treating elevated tHcy along with traditional risk factors to further reduce the burden of first stroke in high-risk populations.